Contraceptive conversations: an observational pilot study to understand, ‘what women prefer and why’ - Meraj, Hina; Khan, Abiha Ahmad; Naaz, Syeda Aamena; Razi, Tuba (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
Background: Contraceptive use is a vital aspect of reproductive health and women's empowerment. Despite national progress in family planning, regional disparities persist, especially in Uttar Pradesh (UP), where contraceptive prevalence remains below the national average. This study explores the preferences and factors influencing contraceptive choices among women in Aligarh, UP. To identify the most commonly preferred contraceptive methods among women aged 18–60 years attending a government hospital in Aligarh and to examine the socio-demographic factors influencing their choices. Methods: A retrospective cross-sectional study was conducted using hospital records from Mohan Lal Gautam Rajkiya Mahila Chikitsalaya, Aligarh, covering a six-month period (January–June 2024). A total of 3,776 women who sought contraceptive services were included. Data on age, socioeconomic status and contraceptive method used were collected and analyzed using descriptive statistics. Results: The majority of women preferred short-term, non-invasive contraceptive methods. Nirodh (condoms) and Mala N (oral contraceptive pills) were the most commonly used, accounting for 40.88% and 39.43% of usage, respectively. Long-term methods such as IUDs and female sterilization were significantly less utilized (<10%). Preference was influenced by factors such as accessibility, cultural acceptability, ease of use and government promotion. Middle and lower-middle socioeconomic groups formed the largest segments of users and women aged 29–39 represented the highest age group seeking contraception. Conclusions: The study highlights a clear preference for reversible, user-controlled contraceptives among women in UP, shaped by ease of access, affordability and minimal side effects. Government initiatives have played a pivotal role in promoting these methods. However, low uptake of long-term options indicates the need for enhanced education, counselling and culturally sensitive awareness programs to broaden contraceptive choices and support informed decision-making.